Nucleic acid binding properties of major proteins from the heterogeneous nuclear ribonucleoproteins of wheat. - Raziuddin (1982)
Glycine-rich core hnRNP proteins purified from wheat bind tightly to single-stranded but not to double-stranded nucleic acids with a preference for natural RNA over single-stranded DNA. Binding results in i) a progressive disruption of the residual secondary structure of the polynucleotide and the formation of an extended nucleoprotein filament until a protein to polynucleotide weight ratio of about 5:1 is attained. As more protein is added, this is followed by ii) the formation of globular structures along the polynucleotide chain with a concomitant reduction in the contour length of the nucleoprotein complex. These two features of the interaction--unwinding and condensation into beads--are analogous to the previously described behavior of the major glycine-rich core hnRNP protein from Artemia salina (Thomas et al. (1981) Proc. Natl. Acad. Sci. USA 78, 2888) and may represent the basic functional properties of this relatively well conserved group of nuclear proteins.